The Influence of Financial Literacy, Ease of Transaction and Financial Capability on Generation Z's Interest in Using Digital Wallet (ShopeePay) in Bangsal Village, Mojokerto Regency - Dewi, Silvia Nirmala; Amaniyah, Evaliati (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
Silvia Nirmala Dewi, The Influence of Financial Literacy, Ease of Transaction and Financial Capability on Generation Z's Interest in Using Digital Wallet (ShopeePay) in Bangsal Village, Mojokerto Regency. Under the guidanceof Hj. Evaliati Amaniyah, S.E., M.S.M. The purpose of this study was to determine the effect of financial literacy, ease of transaction and financial capability on generation Z's interest in using digital wallets Shopeepay in Bangsal Village, Mojokerto Regency. The population selected was generation Z in Bangsal Village, the sample was selected using purposive sampling technique and 100 respondents were selected, this type of research is quantitative. The data used in the study were obtained by distributing questionnaires. The data analysis technique consists of testing the requirements of the research instrument, classical assumption test, multiple linear regression analysis and hypothesis testing using SPSS 25 software tools. The results of this study indicate that each independent variable, namely financial literacy (X₁), ease of transaction (X₂) and financial capability (X₃) partially has a positive and significant effect on interest in using the ShopeePay digital wallet for generation Z in Bangsal Village, Mojokerto Regency.